Scientific Library Between Open and Corporate Science - A. E. Rykhtorova (Библиосфера)
The concept of Open science comes into conflict with the established practice of commercializing the results of research and development work. Commercialization of scientific achievements is both a way to attract funding and a deterrent to intensify the exchange of knowledge and the pace of innovation, especially in basic research. The principles of Open science, providing the ability to widely use and reuse the same data, comparing different approaches and accelerating the development of new research methods, make patenting applied developments much more difficult due to leveling the novelty of inventions in publications and open research data. The purpose of the article is to suggest the possibilities for scientific library to participate in the processes of production, exchange and dissemination of information and knowledge within the framework of the movement of science from the binary system “corporate science vs open science” to hybrid mechanisms of work. Such participation is based on the existing practices of the Centers for Legal and Technical Information and the efforts of scientific library to create an open scientific infrastructure. It involves the expansion of ongoing practices, taking into account the proposed by hybrid science differentiation of Open access to fundamental research and patenting applied developments. Thus, these opportunities are necessary for further modeling the place of scientific library in the ecosystem of open science.